Reimagining Industry 5.0: Centering People in a Digital World and Bridging Techno-Economic and Socio-Technical Futures - Abdullah, Assyari; Sumaiyah, Sumaiyah; Yazid, Yasril; Jayus, Jayus; Khairi, Akmal; Mustafa, Mustafa; Astuti, Dwi Sutri; Edison, Edison; Soim, Muhammad (ARISTO, 2026)
his book review critically examines Industry 4.0 to Industry 5.0: Explorations in the Transition from a Techno-economic to a Socio-technical Future as an intellectual map of the shift from a techno-economic logic (efficiency, productivity, automation) toward a socio-technical horizon that uses human-centricity, sustainability, and resilience as its primary compass. The review synthesizes key threads across chapters—covering conceptual distinctions between Industry 4.0 and 5.0, governance and power dynamics, AI developments (including generative AI), soft skills, circular-economy pathways, and systemic risk pressures (climate crisis, cyber threats, geopolitical volatility) that shape organizational and policy choices. While the book’s main strength lies in its breadth and interdisciplinary ambition, the review highlights areas that would benefit from sharpening: clearer definitional boundaries, more operational indicators to prevent “human-centered, sustainable, resilient” from remaining a slogan, and richer empirical mini-cases—especially beyond Europe/US contexts. Overall, the draft positions the book as a timely bridge between technological acceleration and socio-environmental accountability, and it advances a policy-centric research agenda centered on a core question: technology for whom, under which incentives, and with what social impacts.